PERAN PRICE TO BOOK VALUE SEBAGAI INDIKATOR VALUASISAHAM PADA PERUSAHAAN YANG TERDAFTAR DALAMJAKARTA ISLAMIC INDEX PERIODE 2024 - Nabil Fairil Renata; R. Dimas Aditya; Muhammad Aditya; Mukhtaruddin (PT. Saha Kreasi Indonesia, 2025)
This study analyzes the use of Price to Book Value (PBV) as an instrument in assessing the value of shares traded on the stock exchange for companies listed on the Jakarta Islamic Index (JII) during 2024. The method used here is quantitative with a descriptive-comparative approach, relying on purposive sampling. Secondary data were obtained from annual financial reports and stock price information sourced from the Indonesia Stock Exchange (IDX). The main focus of this study is on the distribution of PBV and stock price grouping (undervalued, fairly valued, overvalued) to evaluate the extent to which PBV reflects the market's assessment of a company's book value. The findings of this study reveal variations in stock values among verified companies on the JII, where out of ten companies with sufficient trading liquidity, five were identified as undervalued and the other five as overvalued. This shows that PBV is useful in identifying patterns of market valuation of stocks, although it does not always accurately reflect fundamental conditions. This study confirms that PBV is an important valuation tool for investors, but it must be combined with other measures and observed over the long term to minimize the possibility of biased conclusions. Recommendations for further research include the use of various valuation measures and observation over a longer period of time.